Comfort: theoretical contribution to nursing - Martins, Ana Gonçalves (2022)
Objective: The objective of this study is to understand how Kolcaba’s Theory of Comfort has influenced research and clinical practice in nursing through the evolution of the concept. Development: This is a study of theoretical nature, resulting from the reading, analysis and reflection of different studies obtained through the literature review conducted in December 2021 in Lisbon, Portugal. The literature evidences the presence of the construct integral to several nursing taxonomies throughout time, and more recently, in several nursing theories. From the conceptual analysis, whatever the theoretical perspective, it is reaffirmed to be a phenomenon of interest, complex and multifaceted. Conclusion: It is understood that this reflection allows us to understand the phenomenon of comfort and how this concept has been studied and clarified, affirming its importance for the quality of nursing care.